Diet of the neotropical lizard Liolaemus polystictus (Squamata: Liolaemidae) from the central Andes, Huancavelica, Peru - Olivera Jara, Diego Alfonso (2020)
This study assessed the diet of the Neotropical lizard Liolaemus polystictus from Huancavelica region in the Peruvian central Andes. The diet composition was identified from 54 sample stomach contents. Percentage of vegetable content was higher than the animal one (V% animal content= 22.97 and V% vegetable content= 77.03), and arthropods were the highest animal content with ten foods items. Within the animal content, Coleoptera were the most representative (N%= 32.05, FO= 59.26 and V%= 41.36%). No animal category showed high IRI values to be considered fundamental. There were not significant differences on prey selection between males, females and juveniles, and on vegetal volumetric contents between adults and juveniles. However, vegetal volumetric contents were significantly different between males and females. Significant differences were found between prey length, width and volume and L. polystictus male head width (AC). Finally, we propose L. polystictus to be considered an herbivorous species, which bring to eight the number of species in the L. montanus group that feed mainly on vegetation.